From the N‐Heterocyclic Carbene‐Catalyzed Conjugate Addition of Alcohols to the Controlled Polymerization of (Meth)acrylates. Issue 26 (26th May 2015) - Ottou, Winnie Nzahou; Bourichon, Damien; Vignolle, Joan; Wirotius, Anne‐Laure; Robert, Fredéric; Landais, Yannick; Sotiropoulos, Jean‐Marc; Miqueu, Karinne; Taton, Daniel
Abstract Among various N‐heterocyclic carbenes (NHCs) tested, only 1, 3‐bis(tert‐butyl)imidazol‐2‐ylidene (NHCtBu) proved to selectively promote the catalytic conjugate addition of alcohols onto (meth)acrylate substrates. This rather rare example of NHC‐catalyzed 1, 4‐addition of alcohols was investigated as a simple means to trigger the polymerization of both methyl methacrylate and methyl acrylate (MMA and MA, respectively). Well‐defined α‐alkoxy poly(methyl (meth)acrylate) (PM(M)A) chains, the molar masses of which could be controlled by the initial [(meth)acrylate]0/[ROH]0 molar ratio, were ultimately obtained in N, N‐dimethylformamide at 25 °C. A hydroxyl‐terminated poly(ethylene oxide) (PEO‐OH) macro‐initiator was also employed to directly access PEO‐b‐PMMA amphiphilic block copolymers. Investigations into the reaction mechanism by DFT calculations revealed the occurrence of two competitive concerted pathways, involving either the activation of the alcohol or that of the monomer by NHCtBu.